Using the Workload Indicators of Staffing Need (WISN) Method for Predicting Pharmacists Human Resources in Hospitals - Putranto Manalu; Mita Sahara; Tan Suyono; Milka Rositi Sianipar (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Pharmacy installation is one of the work units that has a high workload in the hospital. It is critical to measure the number of pharmacists needed to avoid inappropriate workloads and ultimately impact on work stress and impact on patient safety. This study analyzes the demand for energy in pharmaceutical installations using the WISN method. This research is a qualitative descriptive study. Collecting data through observation, interviews, and document review. The results of calculations using the WISN method show a ratio of 0.7 and it can be concluded that the current number of pharmacists is still lacking. The current number of human resources in the pharmacy installation is 29 people. The total need for pharmaceutical personnel according to the WISN formula is 41 people, so that the shortage of pharmaceutical personnel is 11 people. It is recommended for hospital management to determine the duties and functions in accordance with the SOP because there are several nonproductive activities performed by officers at the pharmacy installation. Meeting the number of HR shortages through recruitment can be a way to reduce the workload of pharmaceutical workers. Giving appreciation and additional incentives be considered by the hospital management, given the increased workload.Abstrak: Instalasi farmasi merupakan salah satu unit kerja yang memiliki beban kerja cukup tinggi di rumah sakit. Pengukuran jumlah kebutuhan tenaga farmasi sangat penting untuk dilakukan agar tidak terjadi beban kerja yang tidak sesuai dan pada akhirnya berdampak terhadap stress kerja ser-ta berdampak kepada keselamatan pasien. Penelitian ini bertujuan untuk menganalisis kebutuhan tanaga di instalasi farmasi dengan menggunakan metode WISN. Penelitian ini merupakan penelitian deskriptif kualitatif. Pengumpulan data melalui observasi, wawancara, dan telaah dokumen. Hasil perhitungan dengan metode WISN menunjukkan rasio sebesar 0,7 dan dapat disimpulkan jumlah tenaga farmasi saat ini masih kurang. Jumlah SDM yang ada di instalasi farmasi saat ini adalah 29 orang. Total kebu-tuhan tenaga kefarmasian menurut rumus WISN adalah sebanyak 41 orang, sehingga kekurangan jumlah tenaga kefarmasian adalah 11 orang. Disarankan bagi pihak manajemen rumah sakit untuk menentukan tugas dan fungsi sesuai dengan SOP karena adanya beberapa kegiatan non produktif yang dilakukan oleh petugas di instalasi farmasi. Pemenuhan jumlah kekurangan SDM melalui perekrutan dapat menjadi keluar untuk pengurangan beban kerja tenaga kefarmasian. Pemberian apresiasi dan penambahan insentif mungkin dapat dipertimbangkan oleh pihak mana-jemen rumah sakit, mengingat beban kerja yang semakin meningkat